Vagal threshold determination. Effect of age and gender - Botek, M; Stejskal, P; Krejci, J; Jakubec, A; Gaba, A (International journal of sports medicine, 2010)
Progressive increases in exercise intensity cause significant decreases in vagal activity (VA) until a critical point called the vagal threshold (TVA) is reached. This is where further increases in exercise intensity cause negligible change in VA. This study was designed to develop the algorithm for the TVA determination and to assess the effects of age and gender on its level. The sample consisted of 40 subjects who were divided according to age and gender into 4 groups with 10 subjects each: G1-Men age 25-31, G2-Men age 40-57, G3-Women age 24-28, and G4-Women age 43-56. The vagal responses were assessed by spectral analysis of the heart rate variability method while walking on a treadmill in a steady-state at intensities of 20-70% of the maximal heart rate reserve (MHRR). The mean intensity of 45% MHRR was suggested as the TVA level which is related neither to age nor gender. Heart rate related to TVA (TVA-HR) was affected by gender. High frequency power at TVA was influenced by age. The TVA-HR was considered to be a promising tool for the prescription of a safe level of physical activity for subjects with higher risks of health complications involving elevated sympathoadrenal activity during exercise.
Keywords: dospělí; Female; Age Factors; Adult; mladý dospělý; ženské pohlaví; věkové faktory; lidé; Algorithms; srdeční frekvence; Humans; Middle Aged; Sex Factors; nervus vagus; spektrální analýza; Male; sexuální faktory; Exercise Test; Young Adult; algoritmy; Vagus Nerve; lidé středního věku; mužské pohlaví; Heart Rate; Spectrum Analysis; zátěžový test